Planned Cities. - Keane, Adrienne; Jones, Paul (Palgrave Macmillan, 2020)
The practice of planning cities has come about to create better outcomes for people. Planning comprises two facets – the reasons to plan and the methods of planning – and is known for its interventionist approaches to addressing complex problems. This includes utilising policies, plans and controls over the use of land. Planning in its conservative form is criticised for not responding to the critical issues of equality, liveability and sustainability of cities. The chapter captures these challenges and outlines the key areas of change for planning’s purpose and practices for better cities. In particular, the emphasis is on the rejection of a single, top-down plan that is focused on what a city should be, to bottom-up or community-driven planning decisions; reframing planning to be concerned with the public interest over benefits to a minority; and planning at different spatial scales to enable locally driven responsiveness required to meet sustainability goals.
Keywords: Stadtplanung; Planung; Bodennutzung; Nachhaltige Stadtentwicklung; Bürgerbeteiligung; Lebensqualität